2006
DOI: 10.1007/s10340-006-0138-5
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of several insecticides used for integrated control of Colorado potato beetle (Leptinotarsa decemlineata, Say., Coleoptera: Chrysomelidae)

Abstract: The Colorado potato beetle (Leptinotarsa decemlineata Say.) (CPB) is the main potato pest in Croatia. The main problems in CPB control are related to a number of treatments and resistance development. In order to investigate the efficacy of combinations a reduced dose of spinosad (33% of the full doses) with the reduced doses (33% of full doses) of B.t.t., neem and pyrethrin against CPB larvae, 3-year field trials and one laboratory trial were conducted. Joint actions of the insecticides in combinations were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
24
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 21 publications
6
24
1
Order By: Relevance
“…However, Fitoverm showed the shortest residual activity as compared to Actara, Spinosad, and Mectin. Similarly, Barčić et al (2006) reported a high efficacy of Spinosad against L. decemlineata with a residual activity between 10 and 20 days after treatment. Mandour et al (2008) reported a longer residual activity of Spinosad against Palpita unionalis larvae with a LT 50 of 27.7 days.…”
Section: Residual Actionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, Fitoverm showed the shortest residual activity as compared to Actara, Spinosad, and Mectin. Similarly, Barčić et al (2006) reported a high efficacy of Spinosad against L. decemlineata with a residual activity between 10 and 20 days after treatment. Mandour et al (2008) reported a longer residual activity of Spinosad against Palpita unionalis larvae with a LT 50 of 27.7 days.…”
Section: Residual Actionmentioning
confidence: 84%
“…Fortunately, biological control using biorational insecticides has become the most efficient means in potato pest management programs because their use reduce pollution and delay the development of resistance to other classical insecticides (Barčić et al 2006). Several biopesticide products based on the bacterium Bacillus thuringiensis (Bt) and on the fungal agent Beauveria bassiana have received considerable attention as a potential biological control agent over the last three decades against CPB (Lacey et al 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the level of potato yields on the plants protected by Neem extract, B. bassiana and I. fumosorosea biopreparations was lower than on the chemically protected plants, the differences were not statistically significant, which points to a considerable yield protective role of these preparations in potato cultivation. In contrast, a rather low yield protective efficiency of various combinations of bioinsecticides was demonstrated by Barčcić et al (2006). Assimilation area is a decisive factor for plant productivity and its size depends among others on genetic traits of the species and variety, stage of plant development, plant healthiness and on the climatic conditions (Lepiarczyk et al 2005, Kulig et al 2010, Zarzyńska and Pietraszko 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The applied doses in the first trial are doses used for the control of CPB. Igrc Barčić et al (2006) proved that even a reduced dose of spinosad resulted in significant efficacy on CPB larvae. The control of CPB is mainly targeting larvae.…”
Section: Discussionmentioning
confidence: 99%